2019
DOI: 10.3390/cells8020137
|View full text |Cite
|
Sign up to set email alerts
|

Automodified Poly(ADP-Ribose) Polymerase Analysisto Monitor DNA Damagein Peripheral Lymphocytes of Floriculturists Occupationally Exposed to Pesticides

Abstract: Increased DNA damage and the propension to cancer development, depend on the modulation of the mechanisms to control and maintain genomic integrity. Poly(ADP-Ribose)Polymerase activation and automodification are early responses to genotoxic stress. Upon binding to DNA strand breaks, the enzyme, a molecular DNA nick sensor, is hyperactivated: this is the first step in a series of events leading to either DNA repair or apoptosis. Enzyme hyperactivation and automodification can be easily measured and are widely u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
(38 reference statements)
1
19
0
Order By: Relevance
“…Figure 1 (A) shows the immunological profiles of subjects 1-3 and 5-9 of Table 1. In a previous paper we already evidenced that PARP 2 is particularly abundant in lymphocyte lysates and that the measured PAR-PARP enclosed also automodification of PARP 2 [27,28]. The molecular analysis of the brothers' lymphocytes clearly showed that, compared to the controls, samples had from moderate to very high levels of modified PARP, corresponding to DNA damage of different degrees [28].…”
Section: First Par-parp Analysis In Lymphocyte Lysates Of Elderly Fammentioning
confidence: 71%
See 4 more Smart Citations
“…Figure 1 (A) shows the immunological profiles of subjects 1-3 and 5-9 of Table 1. In a previous paper we already evidenced that PARP 2 is particularly abundant in lymphocyte lysates and that the measured PAR-PARP enclosed also automodification of PARP 2 [27,28]. The molecular analysis of the brothers' lymphocytes clearly showed that, compared to the controls, samples had from moderate to very high levels of modified PARP, corresponding to DNA damage of different degrees [28].…”
Section: First Par-parp Analysis In Lymphocyte Lysates Of Elderly Fammentioning
confidence: 71%
“…The follow up on 2009 (profiles not shown), confirmed this trend. It is worth noting the very high n6/n3 unbalance measured for the subject 9F (27) (Table 4), the woman who developed a gastric carcinoma and deceased at the end of 2009.…”
Section: Anamnestic and Clinical Datamentioning
confidence: 99%
See 3 more Smart Citations